Contrasting geology and mineralogy of evaporative encrustations in salt-tolerant ecosystems, Maniototo basin, Central Otago, New Zealand. Issue 4 (2nd October 2022) - Craw, Dave; Rufaut, Cathy; Kerr, Gemma; Pillai, Dhana
ABSTRACT: Evaporative mineral encrustations have formed on bare substrates at three different sites in the Maniototo basin. Two sites, at Patearoa and Belmont have salts derived primarily from marine aerosols. The Patearoa site has developed on clay-rich pans formed on a terrace eroded by the Taieri River into clay-altered schist basement, and dissolution of albite from altered schist has resulted in precipitation of sodium carbonate with halite, at pH∼10. The Belmont site lies on the flat distal part of an active alluvial fan, and halite-dominated salt encrustations develop on thin dry crusts through capillary action from below. At the nearby Hamiltons historic placer gold mine, excavations exposed clay-altered schist basement beneath Eocene auriferous sediments. Highly fractured and hydrothermally altered fault zones dominate basement, with secondary ankeritic carbonate and pyrite. Water-rock interaction of shallow groundwater in the basement leads to enrichment in dissolved Mg and sulphate that overshadows the marine aerosol components, and evaporative encrustations are dominated by Mg-rich minerals including brucite and epsomite. The halite-dominated sites host rare halophyte ecosystems, but progressive colonisation by adventive species will eventually cover the bare saline substrates. Similar colonisation at the Hamiltons site will result in natural rehabilitation of the abandoned mine site.